2019
DOI: 10.1155/2019/8065376
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Safflower Yellow in Early Diabetic Nephropathy: A Meta-Analysis

Abstract: Background. Diabetic nephropathy (DN) is a major cause of end-stage renal disease. In order to palliate renal function impairment and reduce kidney related mortality, it is crucial to treating DN patients at the early stage. This study aims to assess the efficacy and safety of conventional therapy combined with safflower yellow versus conventional therapy alone in early DN patients. Methods. A meta-analysis of randomized controlled trials that compared safflower yellow plus conventional therapy with convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…The pooled results indicated that the intravenous infusion of HSYA can significantly improve oxidative stress and the inflammatory response and could produce a better therapeutic effect than conventional Western medicine alone. The results in this meta-analysis also showed that the effect of HSYA can significantly reduce the level of SCR and UAER, which is consistent with the results reported by other meta-analyses (Jin et al, 2019;Wang et al, 2019b). Moreover, no adverse effects occurring in these clinical trials were reported by researchers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The pooled results indicated that the intravenous infusion of HSYA can significantly improve oxidative stress and the inflammatory response and could produce a better therapeutic effect than conventional Western medicine alone. The results in this meta-analysis also showed that the effect of HSYA can significantly reduce the level of SCR and UAER, which is consistent with the results reported by other meta-analyses (Jin et al, 2019;Wang et al, 2019b). Moreover, no adverse effects occurring in these clinical trials were reported by researchers.…”
Section: Discussionsupporting
confidence: 92%
“…HSYA has been commonly used in treating cardiovascular and cerebrovascular diseases in China and to scavenge oxygen-free radicals, reduce inflammatory infiltration, and inhibit apoptosis ( Xue et al, 2021 ). Recently, several reviews and meta-analyses (SRs/MAs) have indicated that HSYA can significantly improve DKD by enhancing the total effective rate and reducing urinary albumin excretion rates (UAERs), serum creatinine (SCR), and blood urea nitrogen (BUN) levels ( Yang et al, 2018 ; Wang et al, 2019a ; Wang et al, 2019b ; Jin et al, 2019 ; Xu et al, 2019 ). However, the underlying mechanism implicated in the role of HSYA in DKD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Astragalus polysaccharides could protect against STZ-induced diabetic rats through inhibiting the TGF-β/Smad signaling pathway [ 43 ]. Ligustrazine and safflower yellow improve renal function and reduce urine protein excretion in diabetic nephropathy patients [ 41 , 42 ]. Thus, the anti-inflammation and anti-fibrosis for renoprotection could be attributed to the synergic effects of the multi-compounds from BHD, which should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Complications. Diabetic nephropathy (DN) is one of the major micro-vascular complications of diabetes mellitus (DM) disability and death [12,107]. SY can prolong PT.…”
Section: Treatment Of Diabeticmentioning
confidence: 99%
“…Modern pharmacological studies show that SY has several pharmacological activities, which include but are not limited to improving cardiovascular and cerebrovascular diseases, abirritation [ 9 ], regulating lipids [ 10 ], and treating cancer [ 11 ] and diabetic complications [ 12 ]. SY is approved by the Food and Drug Administration of China.…”
Section: Introductionmentioning
confidence: 99%